Portrait of Louis XV of France - Engraving 18th century 02 - Michel-François... (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Portrait of Louis XV of France - Engraving 18th century 02. Portrait of Louis XV of France
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; Patrimoine; Wikimedia Commons